ISLAM GARIS LURUS: KONSTRUKSI IDENTITAS KEAGAMAAN DI MEDIA SOSIAL - Ilal Maisarah (NIHAYAH: Journal of Islamic Studies, 2025)
This study explores the construction of religious identity within the phenomenon of "Straight-Line Islam" as it unfolds on social media, responding to the dynamics of religious expression in the digital era. Using a multidisciplinary approach involving critical discourse analysis, digital ethnography, and visual semiotic analysis, the research maps how Islamic narratives are shaped and communicated by online communities. The findings reveal that content creators frequently employ religious terminologies such as pure tawhid, anti-bid‘ah, and caliphate as ideological symbols to assert differentiation from other groups, thereby constructing a firm and exclusive Islamic identity. Visually, attributes like robes, niqabs, and particular flags are consistently utilized to reinforce group symbolism. The language used in digital communication tends to be persuasive and emotionally charged, amplified by algorithm-driven virality and the popularity of religious figures. This phenomenon influences followers' self-conception, strengthens online group solidarity, and sacralizes social media as a primary platform for da'wah. However, it also contributes to social segregation, intra-faith polarization, and a diminished space for inclusive religious dialogue. Therefore, this article recommends the development of digital religious literacy rooted in tolerance and collaborative engagement between scholars, educators, and religious figures to foster a healthier religious ecosystem in the digital realm.